Amélioration du taux de multiplication in vitro de Jatropha curcas L - Mergeai, G.; Baudoin, JP.; Toussaint, A.; Mezda Mve, SD. (Tropicultura, 2010)
Improvement of the Rate of in vitro Multiplication of Jatropha curcas L. In order to improve the in vitro multiplication rate (number of shoots/explant/subculture) of Jatropha curcas L. axillary nodes taken from young plants of two accessions of this species (originating from Cameroon and Senegal) have been cultivated for three weeks on a MS medium supplemented with 8.87 μM BAP, 4.92 μM IBA, and 30 g/l sucrose at pH 5.7 ± 0.1, and solidified with 0.7% agar. The shoots obtained from each original explant were then transferred to proliferation media (PM) consisting of MS medium supplemented with 2.21 to 8.9 μM BA or 2.21 to 8.9 μM kinetin in combination with 2.46 μM IBA. Each combination was completed with 33.12 μM adenine sulfate, 82.92 μM of glutamine and 30 g / L sucrose. The best multiplication rate was obtained for the PM medium containing 6.65 μM BA and 2.46 μM AIB. On this medium 42.72 ± 3.22 and 38.15 ± 4.7 shoots/explant were obtained respectively for the accessions from Cameroon and Senegal after 6 weeks of culture, and the mean multiplication rates were 8.27 ± 1.27 (accession from Cameroon) and 7.89 ± 1.13 (accession from Senegal) shoots per explant during the 7 following subcultures (3 weeks/subculture). This medium was also the one that allowed the best overall growth in shoot height. Leafy shoots obtained have been rooted in a medium containing half of the major mineral components of MS supplemented with 5.7 μM IBA, 1.5% sucrose and solidified with 0.7% agar, then acclimated with a survival rate of 97%. These results allow considering the establishment of industrial units of plantlet multiplication from elite clones of Jatropha curcas.